The Representative Utterances Used In The TranslationOf Forty Prophetic Traditions Of An-Nawawi - Handayani, Munawaroh Tri; , Dr. Maryadi, M.A; , Dra. Siti Zuhriah Ariatmi, M.Hum (2015)
This study focuses on analyzing the type of representative utterances using the theory or pragmalinguistic by Anna Trosborg. This study aims at describing 1) the pragmalinguistic form found in "Translation of Forty Prophetic Tradition of An-Nawawi", 2) the illocutionary act of the representative utterances found in "Translation of Forty Prophetic Tradition of An-Nawawi". This research applies descriptive qualitative method. The data are a book of Forty Prophetic Tradition of An-Nawawi. The documentation method is used here to collect the data. The data analyzed are representative utterances found in Forty Prophetic Traditions of An-Nawawi. The results of pragmalinguistic form show that there are 41% or 13 data of intensifiers, 25% or 8 data of commitment up grader, 9% or 3 data of lexical intensification, 6% or 2 data of hedges, 3% or 1 datum of subjectiviziers, 9% or 3 data of cajolers, 3% or 1 datum of appealers, 3% or 1 datum of providing evidence. The result of intention by using illocutionary act by using theory of Kreidler are 2,6% or 1 datum of announcing, 2,6% or 1 datum of declaring, 7,9% or 3 data of explaining, 2,6% or indicating, 7,9% or 3 data of mentioning, 2,6% or 1 datum of reporting, 23,7% or 9 data of affirming, 7,9% or 3 data of asserting, 2,6% or 1 datum of guarantying, 5,3% or 2 data of swearing, 28,95 or 11 data of emphasizing, 2,6% or 1 datum of intimating, 2,6% or 1 datum of predicting.